Trajanje pravdnega postopka, končanega pred pravdnim oddelkom Okrožnega sodišča v Ljubljani, v luči Lukende - Ocepek, France (Pravnik, 2013)
One of the most burning problems of the modern Slovenian society is the judiciary system's efficiency, within which the process time of resolving court disputes is evidently exposed. This got its formal and impartial judgment with the European Court of Human Rights' ruling in the case Lukenda vs. Slovenia on 6 October 2005, according to which Slovenia was sentenced to damages for excessive length of civil litigation trial. Authors were looking for the elements impacting the duration of civil litigation trial by analysing cases that proceeded In Ljubljana District court civil Litigation department (the largest department of its kind in Slovenia). Research frame is limited by microelements that are available in particular lawsuit court file and are main basis for establishing state liability for court backlogging.This statistical research was the first to cover classical lawsuit proceedings in Slovenia; previously Bošnjak and others (2005) have been researching criminal case proceedings.
Keywords: človekove pravice; human rights; pravdni postopek; Slovenia; Slovenija; sodišča; sodni postopek; trajanje